Effect of Distraction Arthroplasty in the Treatment of Moderate‐to‐Severe Ankle Arthritis - Jian Wang; Chenhan Wang; Xiaoheng Ding; Quanyu Dong (Orthopaedic Surgery, 2024)
Objective Currently, the traditional treatment of moderate‐to‐severe ankle arthritis is joint fusion or joint replacement. The aim of this article is to explore the clinical efficacy of distraction arthroplasty in the treatment of moderate‐to‐severe ankle arthritis. Methods A retrospective analysis was conducted with a total of 34 cases who were diagnosed with moderate‐to‐severe ankle arthritis and treated by distraction arthroplasty from January 2007 to November 2021. The average age was 42.3 years. The American Orthopaedic Foot and Ankle Society (AOFAS) ankle–hindfoot score and pain visual analog scale (VAS) were used to evaluate ankle pain and functional improvement before surgery and at the last follow‐up. Based on age, the patients were divided into the ≤45‐year‐old group [young group, 15 cases, age (36.37 ± 4.31) years old] and the >45‐year‐old group [middle‐aged and elderly group, 19 cases, age (53.74 ± 3.17) years old]. The analysis included comparing preoperative and postoperative AOFAS ankle–hindfoot and VAS scores and the influence of age on distraction arthroplasty. Results All 34 patients were followed up, and the follow‐up time ranged from 13 to 143 months, with an average of 45.3 months. The follow‐up times for the young and middle‐to‐elderly groups were (33.19 ± 21.37) months and (55.63 ± 29.69) months, respectively. At the last follow‐up, the AOFAS ankle–hindfoot and VAS scores were significantly improved compared with the preoperative assessment (p < 0.05). According to the etiological analysis, except for Pilon fracture, which showed no differences pre‐ and postoperation in the AOFAS ankle–hindfoot score and VAS score (p > 0.05), all other patients showed significant differences in these two scores (p < 0.05). The difference in preoperative AOFAS ankle–hindfoot scores between the young and middle‐to‐elderly groups was statistically significant (t = 3.422, p = 0.021). The preoperative and postoperative comparison of preoperative VAS scores, AOFAS ankle–hindfoot scores, and VAS scores before and after surgery showed no differences (p > 0.05). The joint space width (JSW) of 10 patients who were followed up for more than 5 years was (2.9 ± 0.5) mm. Two patients who were followed up for more than 10 years showed 3.3 and 3.0 mm, respectively, JSW. Conclusion Distraction arthroplasty with the Ilizarov external fixator can achieve satisfactory results in the treatment of moderate‐to‐severe ankle arthritis (except arthritis caused by Pilon fracture surgery). Age has no statistical impact on the efficacy of distraction arthroplasty.